2022
DOI: 10.1111/chso.12560
|View full text |Cite
|
Sign up to set email alerts
|

Association of parenting behaviours and online risk‐taking in adolescents with ADHD

Abstract: This study explored the role of caregivers in promoting Internet safety among adolescents (n = 58; 13–16 years old) diagnosed with attention‐deficit/hyperactivity disorder in the United States. Teen participants reported their cyberbullying and sexting behaviours and their parents’ knowledge and monitoring of their online activities; parent‐reported opposition‐defiant disorder symptoms were also collected. Teens reported their parents monitored their Internet behaviours in a variety of ways; however, the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…When examining the relationship between the Conners Parent Rating Scale scores and online sexual victimization and risky sexual behaviors in adolescents with ADHD, it was found that adolescents who were victims of online sexual victimization had signi cantly higher average scores on the Oppositional, Social Problems, and Emotional Lability subscales compared to adolescents who were not victims of online sexual victimization. Previous studies have shown that oppositional behavior in adolescents with ADHD is closely associated with risky behaviors and conduct disorders (41,51). We believe that oppositional behaviors may predispose individuals to becoming more vulnerable to online sexual victimization due to a lack of control and becoming easy targets in social environments.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…When examining the relationship between the Conners Parent Rating Scale scores and online sexual victimization and risky sexual behaviors in adolescents with ADHD, it was found that adolescents who were victims of online sexual victimization had signi cantly higher average scores on the Oppositional, Social Problems, and Emotional Lability subscales compared to adolescents who were not victims of online sexual victimization. Previous studies have shown that oppositional behavior in adolescents with ADHD is closely associated with risky behaviors and conduct disorders (41,51). We believe that oppositional behaviors may predispose individuals to becoming more vulnerable to online sexual victimization due to a lack of control and becoming easy targets in social environments.…”
Section: Discussionmentioning
confidence: 79%
“…While some studies suggest that inattention, impulsivity, and hyperactivity are risk factors for online sexual victimization, there is no study that directly compares them with the severity of ADHD symptoms. (51,52). In a study in the literature that investigated the relationship between ADHD-diagnosed adolescents and problematic internet use and gaming disorder using the Conners Parent Rating Scale, only the inattention subscale score was found to be associated with these behaviors (53).…”
Section: Discussionmentioning
confidence: 99%